HOW DOES INTERNATIONAL TRADE REGULATION ADDRESSES EXCHANGE RATES MEASURES? - Vera Thorstensen; Carolina Müller (Revista Direito GV)
ABSTRACT This is study seeks to analyze the international trade regulatory framework regarding exchange rate measures that bear an impact on trade. The present article will explore how the exchange rate issue relates to the WTO and affects its instruments and principles and, in the following, will look for provisions under the WTO agreements that could address the exchange rate issue and rebalance the impacts caused by misaligned currencies on trade.